Sekuritisasi Tradisi Night Hunting (Bomena): Respon terhadap Ancaman Human Security di Bhutan - Agustiansyah, Muhammad Feizal; Trihartono, Agus; Sunarko, Bagus Sigit (University of Jember, 2024)
Tradition is an aspect of culture that is preserved and passed down from generation to generation. Tradition is also known as a concept that defines the identity and uniqueness of a society, as well as being a source of security. Tradition is something that is praised, glorified, and associated with something good in a particular custom or area and is considered sacred. However, in Bhutan there is a tradition called the Bomena tradition. This tradition is also a cycle of sexual exploitation that society cannot break. Various protection efforts have been carried out by the Bhutanese Government, NGOS, and even local community organizations, but this tradition is still carried out today. By using the Buzan concept of human security and securitization, this research wants to analyze the process of securitization of the Bomena tradition, which initially became a tradition in society until it became a dangerous traditional practice that became a threat to human security in Bhutan. Keywords: Bomena Tradition, Tradition, Bhutanese Government, Women, Human Security, Securitization